HBSC Ireland and the public health community: partnerships and processes. (30th September 2020) - NicGagbhainn, S; Kelly, C; Gavin, A; Molcho, M; Kolto, A
Abstract: When HBSC Ireland data was first collected in 1998, very few data on children's health was available. HBSC was seen as an opportunity for Public Health Practitioners and policy-makers to move towards evidence-informed practice. Public health practitioners are invited to liaise with the research team on questionnaire content. HBSC Ireland collaborates to ensure scientifically appropriate measures that can also assist in meeting policy goals. In 2014 the researchers worked with the policy lead for Tobacco to assess children's exposure to tobacco smoke & their views of cigarette packaging. Findings were used to provide a rationale for new legislation on plain packaging for tobacco products and provide a baseline for policy evaluation. In 2018 we worked with the Health Research Board Evidence Centre to develop items on alcohol procurement and location of consumption. A partnership with the Institute of Public Health lead to the inclusion of new items on exposures to UV light and sun protection. This work is being used to develop public health messaging for children and parents by the national cancer control programme. A strategic partnership between HBSC Ireland and the Department of Children and Youth Affairs has enabled the extensive use of HBSC data in the monitoring of the Better Outcomes, Brighter Futures policy framework for children & young people. This has included adopting existing international survey items as indicators and developing new items to fill gaps in the available evidence base. The core principles of these initiatives include transparency; background conceptual & methodological materials are prepared & pilot studies are published. A key element of Knowledge Translation work is our helpdesk, providing analyses to public & community bodies for the purposes of practice, research or policy. More than 50 short reports have been provided as part of this service to the public health community in Ireland.